2018
DOI: 10.1183/20734735.027018
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and emerging topics in lung transplantation

Abstract: Lung transplantation provides a realistic hope of improved survival and enhanced quality of life. However, outcomes can be disappointing, meaning many decisions are highly controversial. Practice is largely based on expert opinion and there is a dearth of high-level evidence. Not surprisingly, this leads to centre-specific practices that may vary considerably in controversial areas. The aim of this review, therefore, is to explore some of those domains and present the available evidence. As the science of lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Three excellent reviews were dedicated to the history, current state, and controversies in lung transplantation (LTx) and perioperative care. [1][2][3] Donor Management Donor Age. Retrospective analysis of United Network of Organ Sharing (UNOS) data suggested that recipients younger than 50 years old had a survival benefit if they received lungs from a donor younger than 60 years old (5-year survival of 52% vs 44%; P < .001).…”
Section: Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three excellent reviews were dedicated to the history, current state, and controversies in lung transplantation (LTx) and perioperative care. [1][2][3] Donor Management Donor Age. Retrospective analysis of United Network of Organ Sharing (UNOS) data suggested that recipients younger than 50 years old had a survival benefit if they received lungs from a donor younger than 60 years old (5-year survival of 52% vs 44%; P < .001).…”
Section: Lung Transplantationmentioning
confidence: 99%
“…The PCC group received a median dose of 703 units pre-CPB and 1405 units post-CPB, for a median total dose of 2108 units. [5][6][7][8][9][10]; P < .001), and packed red cells (5 [3][4][5][6][7] vs 2 [1.25-2.75]; P < .001) and had a shorter time to chest closure (619 vs 548 minutes; P = .008). There were no differences in platelet transfusion, ICU stay or hospital LOS, acute kidney injury (AKI), or mortality.…”
Section: Prothrombin Complex Concentrate (Pcc)mentioning
confidence: 99%
“…Only 10%-15% of lungs procured are judged clinically suitable for transplantation because of a subjective but rigorous selection process based on physician experience and physiological parameters. 1 Despite efforts to optimize clinical outcomes, recipients continue to be at risk because of posttransplantation complications such as primary graft dysfunction (PGD), 2 which occurs in up to 20% of lung transplant patients. Persuasive evidence suggests that oxidant stress from ischemiareperfusion (IR) injury contributes to the evolution of PGD.…”
Section: Introductionmentioning
confidence: 99%
“…Given the existence of comprehensive position papers about timing of referral and listing for LTX, as well as a number of excellent focused commentaries, it would seem somewhat churlish to ignore these and to refer all patients with IPF to an LTX center, as if by reflex. [3][4][5] Education of the general physician and thoracic physician in particular is a key plinth of the approach to ensure that all patients who might benefit from LTX have the opportunity to receive a reasoned and informed opinion regarding their potential suitability. Abrogating that responsibility to another team may risk the sense of patient abandonment, whereas this is rarely the case when the primary care physician works closely with the LTX center as part of a broader team approach.…”
mentioning
confidence: 99%